2021
DOI: 10.1038/s41531-021-00194-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of apomorphine infusion in advanced Parkinson’s disease: a real-life study

Abstract: Long-term effects of continuous subcutaneous apomorphine infusion (CSAI) on health-related quality of life (HRQoL) and predictors of CSAI discontinuation are poorly known. Data from consecutive advanced Parkinson’s disease patients treated in routine care were retrospectively collected over 24 months after CSAI initiation, with a focus on the 39-item Parkinson’s disease questionnaire (PDQ-39). We determined predictors of CSAI discontinuation and HRQoL improvement using multiple regression analysis. Of the 110 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 51 publications
4
38
2
Order By: Relevance
“…A post hoc analysis of the GLORIA registry found a 12-month discontinuation rate of 17% for stable LCIG monotherapy and 23% for stable LCIG-based polytherapy [7]. In a realworld assessment of patients receiving CSAI, 34% discontinued by month 24, with a mean treatment duration of 7.4 months [18]. In contrast, patients in our study receiving CSAI had a 24-month continuation rate of 53.8% and a mean treatment duration of 42.4 months.…”
Section: Discussioncontrasting
confidence: 59%
“…A post hoc analysis of the GLORIA registry found a 12-month discontinuation rate of 17% for stable LCIG monotherapy and 23% for stable LCIG-based polytherapy [7]. In a realworld assessment of patients receiving CSAI, 34% discontinued by month 24, with a mean treatment duration of 7.4 months [18]. In contrast, patients in our study receiving CSAI had a 24-month continuation rate of 53.8% and a mean treatment duration of 42.4 months.…”
Section: Discussioncontrasting
confidence: 59%
“…Previous studies have suggested that the effects of CSAI on dyskinesia are transient [29,30]. The effects of STN DBS on dyskinesia seem to be significant and last longer [19,31].…”
Section: Discussionmentioning
confidence: 94%
“…It is generally considered a likely option in patients with advanced PD [ 182 , 183 , 184 , 185 , 186 ] and has been described as a transitional option between the standard treatment and DBS, providing better control of dyskinesia [ 181 , 187 ]. However, it has sometimes been pointed out, that the increase in LEDD due to combined treatment with oral L-DOPA and CSAI led to a lack of initial improvement in dyskinesias and was a reason for discontinuing therapy [ 181 , 187 , 188 ]. In contrast, this problem was not observed with CSAI used in monotherapy, and the positive effect on dyskinesias was beneficial [ 185 ].…”
Section: Resultsmentioning
confidence: 99%